Development status of electrocatalytic hydrogenation of biomass small molecules and prospects for industrial production - Yuchen Lei; Fuhai Zhang; Wenbin Zhang; Wei Zhao (iScience)
Summary: Biomass is the only renewable organic carbon resource in nature, and utilization of biomass is important for carbon neutrality. Currently, depolymerizing biomass macromolecules into small organic monomers via thermocatalytic pyrolysis is a well-established technique. Further valorization of these biomass small molecules to value-added products has attracted increasing attention, especially via electrochemistry coupling green electricity. Electrocatalytic hydrogenation (ECH) directly uses hydrogen from water and operates under mild conditions (e.g., ambient temperature and pressure), which plays an important role for upgrading biomass small molecules and avoids substantial CO2 emission. In this review, we will provide a summary of recent achievements in ECH of biomass small molecules, with a review focus on the research about pushing ECH toward industrial-scale productivities. We will also discuss the existing problems and challenges in this field and propose an outlook for the future developments.